EFEKTIVITAS TEKNIK MODELING DALAM MENINGKATKAN KEMATANGAN KARIR PESERTA DIDIK - Djoni dan Solihatun Aminudin (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2014)
Abstract: Mechanical modelling is a technique that is implemented from social learning theory. This theory explains how human behavior in terms of continuous reciprocal interaction between cognitive, behavioral, and environmental influences. Learning through modeling include the addition of a search and the observed behavior, and then to generalize from one observation to another observation. This study aims to determine the effectiveness of Modeling Techniques to Enhance Career Maturity Learners SMA PKBM Negeri 12 East Jakarta in class XI in the school year 2013-2014. The method used in this study is the method of experiment. With a design that is used is the Pre-Experimental Design. Forms Pre-Experimental Design used is